Two-Stage Procedure for the Quantitative Determination of Autoprothrombin III Concentration and Some Applications - Reno, Ronald S; Seegers, Walter H (Thrombosis and Haemostasis, 1967)
A two-stage assay procedure was developed for the determination of the autoprothrombin C titre which can be developed from prothrombin or autoprothrombin III containing solutions. The proenzyme is activated by Russell’s viper venom and the autoprothrombin C activity that appears is measured by its ability to shorten the partial thromboplastin time of bovine plasma.Using the assay, the autoprothrombin C titre was determined in the plasma of several species, as well as the percentage of it remaining in the serum from blood clotted in glass test tubes. Much autoprothrombin III remains in human serum. With sufficient thromboplastin it was completely utilized. Plasma from selected patients with coagulation disorders was assayed and only Stuart plasma was abnormal. In so-called factor VII, IX, and P.T.A. deficiency the autoprothrombin C titre and thrombin titre that could be developed was normal. In one case (prethrombin irregularity) practically no thrombin titre developed but the amount of autoprothrombin C which generated was in the normal range.Dogs were treated with Dicumarol and the autoprothrombin C titre that could be developed from their plasmas decreased until only traces could be detected. This coincided with a lowering of the thrombin titre that could be developed and a prolongation of the one-stage prothrombin time. While the Dicumarol was acting, the dogs were given an infusion of purified bovine prothrombin and the levels of autoprothrombin C, thrombin and one-stage prothrombin time were followed for several hours. The tests became normal immediately after the infusion and then went back to preinfusion levels over a period of 24 hrs.In other dogs the effect of Dicumarol was reversed by giving vitamin K1 intravenously. The effect of the vitamin was noticed as early as 20 min after administration.In response to vitamin K the most pronounced increase was with that portion of the prothrombin molecule which yields thrombin. The proportion of that protein with respect to the precursor of autoprothrombin C increased during the first hour and then started to go down and after 3 hrs was equal to the proportion normally found in plasma.